2013
DOI: 10.2355/isijinternational.53.880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti Addition on Weld Microstructure and Inclusion Characteristics of Bainitic GMA Welds

Abstract: The effects of titanium content on weld microstructure and inclusion characteristics have been studied using the two different bainitic welds fabricated to have similar oxygen content. Analytical transmission electron microscopy analysis with thin foil specimens was carried out to investigate inclusion characteristics focusing on the crystal structure and the chemical features of the constituent phases. Then, these results were related with the proportion of acicular ferrite measured under an optical microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This difference appears to be caused by the increased amount of (Mn,Ti)-spinel oxide and may explain why the 2Ti weld has a higher content of AF than the 1Ti weld ( Table 2). The inclusion characteristics of this weld have been reported previously, 14,15) thus this study simply reaffirms the previous results. The inclusions of this weld were composed mainly of two Ti-oxides having different Mn contents and Al-oxide along with a minimal amount of Mn-silicate.…”
Section: Inclusion Phases and Mdz Formationsupporting
confidence: 81%
See 3 more Smart Citations
“…This difference appears to be caused by the increased amount of (Mn,Ti)-spinel oxide and may explain why the 2Ti weld has a higher content of AF than the 1Ti weld ( Table 2). The inclusion characteristics of this weld have been reported previously, 14,15) thus this study simply reaffirms the previous results. The inclusions of this weld were composed mainly of two Ti-oxides having different Mn contents and Al-oxide along with a minimal amount of Mn-silicate.…”
Section: Inclusion Phases and Mdz Formationsupporting
confidence: 81%
“…These phases possessed different concentration of Mn, one of them being thought to be TiO. The present authors 14,15) also found such dual phase inclusions in the weld of 720 ppm Ti, but those phases were all identified as Ti 2 O 3 . In addition, these inclusions were characterized to be fully surrounded by a manganese-depleted zone (MDZ), which has been reported to be effective for AF nucleation in wrought steels.…”
Section: )mentioning
confidence: 68%
See 2 more Smart Citations
“…When titanium oxide precipitates on the surface of refractory inclusion, then zones with reduced content of alloying elements, having high mobility in γ-phase, can be formed in adjacent areas of solid solution. The inclusions of given type are the most efficient centers of nucleation of bainite microstructure [9,10].…”
mentioning
confidence: 99%